Welcome to EICS 2016 - Luyten, Kris (2016)
[Extract] The ACM SIGCHI Symposium on Engineering Interactive Computing Systems (EICS) is a yearly international conference devoted to engineering usable and reliable interactive computing systems. Research presented at EICS revolves around methods, processes, techniques and tools that support specifying, designing, developing, deploying and verifying interactive systems. This 8th ACM SIGCHI Symposium on Engineering Interactive Computing Systems (EICS'16) took place in Brussels, Belgium (21-24 June 2016) – at the heart of Europe...